Health care frames – from Virchow to Obama and beyond. Issue 6 (14th October 2014) - Sturmberg, Joachim P.; O'Halloran, Di; Colagiuri, Ruth; Fernandez, Ana; Lukersmith, Sue; Torkfar, Ghazal; Salvador‐Carulla, Luis
Abstract Rationale, aims, objectives and Methods Framing allows us to highlight some aspects of an issue, thereby bringing them to the forefront of our thinking, talking and acting. As a consequence, framing also distracts our attention away from other issues. Over time, health care has used various frames to explain its activities. This paper traces the emergence of various health care frames since the 1850s to better understand how we reached current ways of thinking and practicing. Results and Conclusions The succession of the most prominent frames can be summarized as: medicine as a social science; the germ theory of disease; health care as a battleground (or the war metaphor); managing health care resources (or the market metaphor); Health for All (the social justice model); evidence‐based medicine; and Obama Care. The focus of these frames is causal, instrumental, political/economic or social in nature. All remain relevant; however, recycling individual past frames in response to current problems will not achieve the outcomes we seek. Placing the individual and his/her needs at the centre (the attractor for the health system) of our thinking, as emphasized by the World Health Organization's International Classification of Function framework and the European Society of Person Centered Health Care, may provide the frame to refocus health and health care as interdependent experiences across individual, community and societal domains. Shifting beyond the entrenched instrumental and economic thinking will be challenging but necessary for the sake of patients, health professionals, society and the economy.